On the uniqueness conditions and bifurcation criteria in coupled thermo-elasto-plasticity - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
The global and local conditions of uniqueness and the criteria excluding a possibility of bifurcation of the equilibrium state for small strains are derived. The conditions and criteria are derived analyzing the problem of uniqueness of solution of the basic incremental boundary problem of coupled generalized thermo-elasto-plasticity. This paper is a continuation of some previous works by the author, but contains new derivation of the global and local criteria excluding a possibility of bifurcation of the equilibrium state for a comparison body dependent on statically admissible fields of stress velocity.
Keywords: bifurcation of the equilibrium state; conditions and criteria of uniqueness; boundary-value problems; generalized coupled thermo-elasto-plasticity; comparison bodies; family of local conditions of uniqueness; parameter of the optimization